Long-Term Renal Function Outcomes in Bladder Cancer After Radical Cystectomy - Takahiro Osawa; Nobuo Shinohara; Satoru Maruyama; Koji Oba; Takashige Abe,; Shintaro Maru; Norikata Takada; Ataru Sazawa; Katsuya Nonomura (Urology Journal, 2013)
PURPOSE: To evaluate postoperative renal function and risk factors for the loss of renal function in patients who had undergone radical cystectomy. MATERIALS AND METHODS:A retrospective single institutional study evaluated 70 patients, including 54 men and 16 women who underwent radical cystectomy. The median follow-up period was 34.5 months (range, 12 to 228 months). In this cohort, four types of urinary diversions were studied, including ilealneobladder (n = 24), ileocecalneobladder (n = 12), ileal conduit (n = 25), and cutaneous ureterostomy (n = 9). Postoperative changes in renal function were reviewed, and the estimated serum creatinine-based glomerular filtration rate (eGFR) was calculated. The variables analyzed were age, a prior history of hypertension or diabetes mellitus, pre-operative renal function, type of urinary diversion, the postoperative occurrence of acute pyelonephritis, and the presence of chemotherapy. RESULTS: The mean eGFR was 74.6 (range, 15.2 to 155.1) mL/min/1.73 m2 before surgery and 63.6 (range, 8.7 to 111.5) mL/min/1.73 m2 at the last follow-up. The 10-year renal deterioration-free interval was 63.8%. Multivariate analysis showed that a postoperative episode of acute pyelonephritis [Odds Ratio (OR), 3.21; 95% Confidence Interval (CI), 1.14 to 9.02; P = .03] and the presence of chemotherapy (OR, 3.27; 95% CI, 1.33 to 8.01; P = .01) were significant adverse factors. CONCLUSION: Twenty-four (34.2%) patients demonstrated reduced renal function during the follow-up period. Postoperative episodes of acute pyelonephritis and the presence of chemotherapy were found to be significant adverse factors.